DINAMIKA LIVE STREAMING COMMERCE: ANALISIS PENGARUH PERSEPSI HARGA, KESADARAN MEREK, DAN KETERLIBATAN PELANGGAN TERHADAP MINAT BELI KONSUMEN - Fahrul Ardani; Siti Aminah; Dewi Deniaty Sholihah (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the influence of Price Perception, Brand Awareness, and Customer Engagement on Purchase Intention for Aerostreet shoes through Shopee Live Streaming in Surabaya. This topic is essential in the field of digital marketing as these three variables play a key role in shaping consumer purchasing decisions, particularly in the increasingly popular context of live streaming e-commerce. The study seeks to provide a deeper understanding of how pricing, brand recognition, and consumer involvement can be optimized by businesses to enhance interest in local products amid intense competition. The research employs a quantitative approach using Partial Least Square (PLS) analysis, processed with SmartPLS software. The sample consists of 90 respondents selected using purposive sampling. Data were collected via an online questionnaire distributed to Shopee users in Surabaya who had previously viewed Aerostreet’s live streaming sessions. The findings reveal that both Price Perception and Brand Awareness have a significant positive effect on Purchase Intention, while Customer Engagement shows a significant negative effect. These results suggest that rational and cognitive factors outweigh emotional engagement in influencing purchase decisions in the live streaming context.